Transport of hybrid type nanomaterials in peristaltic activity of viscous fluid considering nonlinear radiation, entropy optimization and slip effects. (February 2020) - Farooq, S.; Ijaz Khan, M.; Waqas, M.; Hayat, T.; Alsaedi, A.
Highlights: An investigation is carried out regarding the peristaltic flow of hybrid nanofluids in rotating channel walls. Nonlinear thermal radiation and variable viscosity are accounted in presence of slip effects. Convective conditions of heat and mass transfer are satisfied by the channel walls. Fluid is saturated due to the porous characteristics of channel walls. Entropy generation rate is minimum for variable viscosity and maximum for hybrid nanoparticles. Abstract: Background: In last few decades, a new class of working materials which comprises from two solid materials dispersed in a continuous phase liquid was established and deeply scrutinized. These materials are called hybrid nanomaterials. This research article aims to investigate entropy optimization in hybrid nanomaterial flow through a rotating peristaltic channel walls. Flow behavior is analyzed between the channels which is caused by propagation of sinusoidal waves. Viscosity of fluid is considered variable instead of constant characteristics. Fluid saturates through porous attributes of channel walls. Nonliear radiative flux and convective condition are considered. Slip conditions are imposed at the boundary of walls. Methods: Built-in-Shooting technique is employed to obtain the numerical outcomes for the considered flow problem. Results: Impacts of sundry variables on the entropy, temperature and velocity are scrutinized through different graphs. Numerical result presents that the axial velocity escalates with the inclusion of hybrid nanomaterial. The temperature of fluid enhances through higher estimations of hybrid nanoparticles. Conclusions: Here the flow behavior is discussed between the channels which are caused by propagation of sinusoidal waves with speed c. Entropy generation rate is minimum for variable viscosity and maximum for hybrid nanoparticles. Hybrid nanoparticles increase the temperature of fluid. Bejan number presents the similar impact for variable viscosity and thermal slip parameters. Temperature field decays through higher values of Brinkman number.